Ragam Putusan Inkonstitusional Bersyarat Dalam Perkembangan Hukum Di Indonesia - Muhammad Faris Hidayat; Riski; Maulana Mahrus Alam Pamungkas (JURNAL LEGISIA, 2023)
Decions the are condiotinally incontitusional, where as decions of the conditional, Incontitusional type were Introducet several Times throght decision number 4/PUU-VII/2009, however, these use of this condiotinal Incontitusional clauce was implicity used by Jimmy Assidiqie in decision number 026/PUU-III/2005 regarding the review of the 2006 state budget law. It noted that of out 103 condiotinal decisions. 86 other decions where conditional Incontitusional decisions. Based on an analisis of the 86 conditional Incontitusional decions, there are four characteristic of conditional Incontitusional decions, the first condiotinal Incontitusional in the decions there must be a clause contained innyhe decions, the second condiotinal Incontitusional decions has principle that must be based on the grantung decision, this is because the norm being tested is basically Incontitusional, however, the contitucional court has provide that condiotinal Incontitusionality. Then the third condiotinal Incontitusional verdict is a ruling that is meaning full to the norm being tested. Four, the is difference isnsubstance the conditional Incontitusional Clause.